Fundamentals of Creating an Electronic Encyclopedic Dictionary of Linguistic Terms (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article highlights the fundamentals of creating an electronic encyclopedic dictionary of linguistic terms. In world and Uzbek linguistics, research objects and interpretations of these objects are emerging that were unimaginable a few decades ago. In particular, areas such as neurolin guistics, artificial intelligence, linguistic expertise, extreme linguistics, speech influence, corpus linguistics, linguoculturalology, have not been sufficiently studied not only in Uzbek, but also in world linguistics. In this article we pointed our view to the need of creating an electronic encyclopedic dictionary of linguistic terms.